Multi-aperture carbon fiber material, sodium ion battery negative electrode material and preparation method
By adding SiO2 nanospheres and polymethyl methacrylate as templates to the spinning liquid, a multi-porous carbon fiber material was prepared, which solved the problem that non-porous structure carbon fiber material could not provide buffering for sodium ion batteries, and achieved the effect of improving conductivity and electrochemical performance.
Patent Information
- Application Number
- CN202510057571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the carbon fiber material prepared by electrospinning technology has a non-porous structure, resulting in a small specific surface area and is unable to buffer the sodium-decantization and decantation of sodium-ion batteries, affecting the charge and discharge performance.
After electrospinning, pre-oxidation and calcination were performed, SiO2 nanospheres and polymethyl methacrylate were added to the spinning liquid to obtain a multi-porous carbon fiber material.
The prepared multi-porous carbon fiber material has a three-dimensional frame structure, which enhances conductivity, reduces current density, and the stable framework buffers volume changes during charging and discharging, improves electrochemical performance, and shows good cycling stability.
Smart Images

Figure CN119859865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a multi-porous carbon fiber material, a sodium ion battery negative electrode material and a preparation method thereof. Background Art
[0002] In recent years, the large-scale application of energy storage batteries has stimulated the vigorous development of rechargeable batteries other than lithium-ion batteries. Lithium-ion batteries have the advantages of large capacity, high operating voltage and long cycle life, and have become one of the main energy sources for portable electronic devices and electric vehicles. However, due to the increase in market demand, the reduction of lithium resources and the increase in production costs, lithium-ion batteries cannot meet the large-scale market demand in the future.
[0003] Therefore, there is an urgent need to develop the next generation of rechargeable batteries with good safety performance, low cost and abundant raw materials. Since Na and Li are in the same main group, their chemical properties are similar, and Na resources are relatively abundant. Sodium accounts for about 2.75% of the earth's crust, while lithium accounts for only 0.002%. Therefore, sodium-ion batteries have become a potential substitute for lithium-ion batteries.
[0004] However, the ionic radius of sodium ions is 55% larger than that of lithium ions, which makes the structure of active materials easily destroyed during the sodium-de-sodiumization process. The three-dimensional structure of carbon fiber materials gives them good conductivity, but the carbon fiber materials obtained by direct spinning are non-porous structures and have a small specific surface area, which makes them unable to play a buffering role in the sodium-de-sodiumization of sodium-ion batteries. Summary of the invention
[0005] The present invention provides a multi-porous carbon fiber material, a sodium ion battery negative electrode material and a preparation method, which effectively solves the technical problem that the current use of only electrospinning technology will lead to the formation of a non-porous structure of carbon fiber materials, the specific surface area of the carbon fiber material is small, resulting in the inability to play a buffering role for sodium de-sodiumization, thereby affecting the charge and discharge performance of the sodium ion battery. The present invention adopts electrospinning technology to prepare a multi-porous carbon fiber with a three-dimensional framework, which provides a transmission path for the transmission of electrons, enhances the conductivity of the material, and effectively reduces the local current density. The stable skeleton of the carbon fiber buffers the volume change generated during the charge and discharge process, and further improves the electrochemical performance.
[0006] The first object of the present invention is to provide a method for preparing a multi-pore carbon fiber material, characterized in that it comprises the following steps:
[0007] SiO 2 Nanospheres, polymethyl methacrylate and polyacrylonitrile were dissolved in N,N ’-dimethylformamide, mixed at 30°C to 60°C to obtain a spinning solution, and the spinning solution was subjected to electrostatic spinning to obtain nanofibers.
[0008] The nanofibers are pre-oxidized in air at 200°C to 250°C, and then heated to 500°C to 1000°C, and calcined in a protective atmosphere to decompose the polymethyl methacrylate in the nanofibers to obtain SiO coated nanofibers. 2 of carbon fiber.
[0009] The coated SiO 2 The carbon fiber is stirred in an alkaline solution to etch SiO 2 , and obtain a multi-pore carbon fiber material.
[0010] As a preferred embodiment, the SiO 2 The mass ratio of the nanospheres, polymethyl methacrylate and polyacrylonitrile is 1-5:1-5:5.
[0011] As a preferred embodiment, the alkaline solution contains OH - The solution has a concentration of 0.5mol / L~2mol / L.
[0012] As a preferred embodiment, the stirring time is 6h to 24h.
[0013] As a preferred embodiment, the electrospinning conditions are: temperature of 20°C to 40°C, humidity of 40% to 60%, inner diameter of the electrospinning needle of 0.21mm to 1.07mm, collection distance of 10cm to 25cm, voltage of 16kV to 25kV, and propulsion speed of 0.5mL / h to 1.5mL / h.
[0014] As a preferred embodiment, the pre-oxidation time is 2 hours, and the calcination time is 2 hours to 5 hours.
[0015] As a preferred implementation, the heating rate is 1°C / min to 5°C / min.
[0016] The second object of the present invention is to provide a multi-pore carbon fiber material prepared by the above preparation method.
[0017] The third object of the present invention is to provide a sodium ion battery negative electrode material, which is prepared from an active material, conductive carbon black and polyvinylidene fluoride, wherein the active material is the above-mentioned multi-porous carbon fiber material.
[0018] The fourth object of the present invention is to provide a method for preparing the above-mentioned sodium ion battery negative electrode material, comprising the following steps: mixing a multi-porous carbon fiber material, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 7 to 8:1 to 2:1, adding N-methylpyrrolidone, grinding, and coating on a copper foil, drying, and cutting to obtain an electrode sheet with a diameter of 16 mm and a thickness of 0.1 mm.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention uses SiO 2 Nanospheres and polymethyl methacrylate are used as templates of pore structures, dispersed in a spinning solution for spinning, and nanofibers are obtained. The nanofibers are pre-oxidized and calcined to obtain SiO coated nanofibers. 2 The carbon fiber is then etched with an alkaline solution to obtain a carbon fiber material with regular and uniform pores and multiple pores. 2 The content of nanospheres and polymethyl methacrylate controls the pore density and pore size of carbon fiber, and the polymer fiber obtained by electrostatic spinning is converted into carbon fiber by pre-oxidation and calcination, thereby improving the mechanical strength and stability of the fiber. Pre-oxidation partially oxidizes hydrogen, oxygen and nitrogen elements in the polymer fiber to form oxides with a high oxygen content, thereby reducing the amount of gas released during fiber carbonization, reducing the internal stress and thermal shrinkage of the fiber during fiber carbonization, and improving the carbonization efficiency. The pre-oxidized polymer fiber is then pyrolyzed into carbon fiber at high temperature after carbonization. The hard template silica microspheres added during spinning are removed by alkali etching, so that spherical holes are left inside the carbon fiber, thereby increasing the specific surface area of the material. Compared with nano carbon fibers with a single pore size, the hierarchical pores of the multi-aperture carbon fiber of the present invention have higher electronic conductivity, the mesopores provide fast and efficient electron transmission channels, and the macropores increase the specific surface area, so that sodium ions can be stably adsorbed and released.
[0021] The preparation method of the multi-porous carbon fiber provided by the present invention can adjust the pore density and size of the carbon fiber according to the actual application situation. The multi-porous carbon fiber material prepared by the present invention has a three-dimensional framework structure, which provides a transmission path for the transmission of electrons, enhances the conductivity of the material, and effectively reduces the local current density. The stable skeleton of the multi-porous carbon fiber material can buffer the volume changes generated during the charge and discharge process, further improving the electrochemical performance. When the multi-porous carbon fiber material is applied to the negative electrode material of the sodium ion battery, it shows good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the porous carbon fiber material prepared in Example 1 of the present invention.
[0023] Figure 2This is a SEM image of the porous carbon fiber material prepared in Example 2 of the present invention.
[0024] Figure 3 This is a SEM image of the cross section of the porous carbon fiber material prepared in Example 1 of the present invention.
[0025] Figure 4 This is a SEM image of the longitudinal morphology of the porous carbon fiber material prepared in Example 1 of the present invention.
[0026] Figure 5 A sodium ion battery negative electrode material prepared by using the multi-porous carbon fiber material of the present invention is used in a sodium ion battery at 1Ag -1 Cyclic comparison diagram under current density of .
[0027] Figure 6 The figure is a comparison chart of the rate performance of sodium ion batteries using the sodium ion battery negative electrode material prepared using the multi-porous carbon fiber material of the present invention.
[0028] Figure 7 This is a nitrogen adsorption-desorption curve diagram of the porous carbon fiber material prepared in Example 1 of the present invention.
[0029] Figure 8 This is a pore size distribution diagram of the porous carbon fiber material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0031] Regarding what is mentioned in the background technology of the present invention: First, since the ionic radius of sodium ions is 55% larger than that of lithium ions, the structure of the active material is easily destroyed during the sodiumization and de-sodiumization process. Second, although the three-dimensional structure of the carbon fiber material gives it good conductivity, the carbon fiber material obtained by direct spinning is a non-porous structure, and the specific surface area of the carbon fiber material is small, resulting in the technical problem that it cannot play a buffering role in the sodiumization and de-sodiumization of sodium ion batteries. Based on the above technical problems, the present invention provides a multi-porous carbon fiber material, a sodium ion battery negative electrode material and a preparation method.
[0032] The technical solution of the present invention is analyzed and explained below.
[0033] The present invention provides a method for preparing a multi-pore carbon fiber material, comprising the following steps:
[0034] SiO 2Nanospheres, polymethyl methacrylate and polyacrylonitrile were dissolved in N,N ’ -dimethylformamide, stirring at 30°C to 60°C for 6h to 12h, mixing well to obtain a spinning solution, and electrospinning the spinning solution to obtain nanofibers.
[0035] The SiO 2 Nanospheres are made of The method is as follows: NH 3 ·H 2 O, ethanol and deionized water are mixed in a volume ratio of 1-5:60-80:10 to obtain a mixed solution, tetrapropoxysilane is added to the mixed solution in a volume ratio of 4-10:80, stirred at 20°C-70°C for 6h-15h, and centrifuged to obtain SiO 2 Nanospheres.
[0036] The nanofibers are pre-oxidized in air at 200°C to 250°C for 2 hours, then heated to 500°C to 1000°C, and calcined in a protective atmosphere for 2 to 5 hours to decompose the polymethyl methacrylate in the nanofibers to obtain SiO coated nanofibers. 2 of carbon fiber.
[0037] The coated SiO 2 The carbon fiber was stirred in an alkaline solution for 6 to 24 hours to etch SiO 2 , and obtain a multi-pore carbon fiber material.
[0038] In the above preparation method, SiO 2 Nanospheres and polymethyl methacrylate are used as templates of pore structures, dispersed in a spinning solution for spinning, and nanofibers are obtained. The nanofibers are pre-oxidized and calcined to obtain SiO coated nanofibers. 2 The carbon fiber is then etched with an alkaline solution to remove the template material silica, resulting in a multi-porous carbon fiber material with regular and uniform pores. The hierarchical pores of the multi-porous carbon fiber have higher electronic conductivity, the mesopores provide fast and efficient electron transmission channels, and the macropores increase the specific surface area, allowing sodium ions to be stably adsorbed and desorbed.
[0039] In the present invention, the SiO 2 The mass ratio of nanospheres, polymethyl methacrylate and polyacrylonitrile is 1-5:1-5:5. 2 Nanospheres and polymethyl methacrylate are templates added to the spinning solution. They are removed by subsequent calcination and etching, leaving holes. If the template agent is excessive, it will block the spinning needle during spinning, or cause the fiber to break easily and become fragile during the subsequent calcination and etching process. If the template agent is too little, there will be too few holes, and the effect of increasing the specific surface area will not be achieved.
[0040] It should be noted that the alkaline solution contains OH - The solution has a concentration of 0.5 mol / L to 2 mol / L. The template material on the carbon fiber can be effectively removed by reacting at this concentration.
[0041] In order to obtain nanofibers with uniform size and similar performance, the conditions for electrospinning are: temperature of 20℃~40℃, humidity of 40%~60%, inner diameter of electrospinning needle of 0.21mm~1.07mm, collection distance of 10cm~25cm, voltage of 16kV~25kV, and propulsion speed of 0.5mL / h~1.5mL / h. These are the environmental conditions required for spinning. If they are not within this range, spinning will fail. Temperature and humidity will affect the tensile properties and toughness of the fiber. When the temperature is too high and the humidity is too low, the solvent will evaporate prematurely during spinning; when the temperature is too low and the humidity is too high, the solvent will be difficult to evaporate during spinning, and no polymerized fiber can be obtained. Needle diameter, voltage, collection distance, and propulsion speed are the process parameters of spinning. The higher the voltage, the smaller the fiber diameter, the longer the jet distance, and the larger the fiber diameter. The inner diameter of the needle determines the speed and atomization degree of the droplets ejected from the needle. A smaller inner diameter produces finer fibers, but it is easy to cause blockage. If the fiber is too thin, it is easy to not cover the template, and if it is too thick, the template will not be able to react with the subsequent alkaline solution. If the propulsion speed is too fast, the droplets will be sprayed directly, and if it is too slow, the solvent will evaporate at the needle tip, causing the needle tip to be blocked.
[0042] It should be noted that the heating rate is 1°C / min to 5°C / min.
[0043] The technical effects of the present invention are described below in conjunction with specific embodiments and comparative examples.
[0044] Example 1
[0045] A method for preparing a multi-pore carbon fiber material comprises the following steps:
[0046] (1) NH 3 ·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0047] Among them, NH 3 ·H 2 The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0048] (2) SiO 2Nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0049] Among them, SiO 2 The mass ratio of nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile was 3:2:5, the stirring temperature was 50°C, and the stirring time was 12 h.
[0050] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of an electrospinning needle of 0.6 mm, a collection distance of 15 cm, a voltage of 18 kV, and a propulsion speed of 1 mL / h to obtain electrospun nanofibers.
[0051] (4) After the nanofibers in step (3) are carbonized and calcined, they are cooled and ground to obtain SiO 2 @C fiber.
[0052] The carbonization process is as follows: first pre-oxidation at 250°C in air for 2 h, calcination at 800°C in a protective atmosphere for 4 h, and a heating rate of 3°C / min.
[0053] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain multi-pore carbon fiber materials.
[0054] Example 2
[0055] A method for preparing a multi-pore carbon fiber material comprises the following steps:
[0056] (1) NH 3 ·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0057] Among them, NH 3 ·H 2 The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0058] (2) SiO 2 Nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0059] Among them, SiO 2The mass ratio of nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile was 4:1:5, the stirring temperature was 50°C, and the stirring time was 12 h.
[0060] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of an electrospinning needle of 0.5 mm, a collection distance of 17 cm, a voltage of 20 kV, and a propulsion speed of 1.3 mL / h to obtain electrospun nanofibers.
[0061] (4) After the carbonization and calcination of the nanofibers in step (3), the nanofibers are cooled and ground to obtain SiO2@C fibers.
[0062] The carbonization process is as follows: first, pre-oxidation at 200°C in air for 2 h, and calcination at 600°C in a protective atmosphere for 5 h, with a heating rate of 3°C / min.
[0063] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain multi-pore carbon fiber materials.
[0064] Example 3
[0065] A method for preparing a multi-pore carbon fiber material comprises the following steps:
[0066] (1) NH 3 ·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0067] Among them, NH 3 ·H 2 The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0068] (2) SiO 2 Nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0069] Among them, SiO 2 The mass ratio of nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile was 2:3:5, the stirring temperature was 50°C, and the stirring time was 12 h.
[0070] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of the electrospinning needle of 0.67 mm, a collection distance of 14 cm, a voltage of 17 kV, and a propulsion speed of 1.5 mL / h to obtain electrospun nanofibers.
[0071] (4) After the nanofibers in step (3) are carbonized and calcined, they are cooled and ground to obtain SiO 2 @C fiber.
[0072] The carbonization process is as follows: first, pre-oxidation at 200°C in air for 2 h, and calcination at 700°C in a protective atmosphere for 3 h, with a heating rate of 3°C / min.
[0073] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain multi-pore carbon fiber materials.
[0074] Example 4
[0075] A method for preparing a multi-pore carbon fiber material comprises the following steps:
[0076] (1) NH 3 ·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0077] Among them, NH 3 ·H 2 The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0078] (2) SiO 2 Nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0079] Among them, SiO 2 The mass ratio of nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile was 1:4:5, the stirring temperature was 50°C, and the stirring time was 12 h.
[0080] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of an electrospinning needle of 0.4 mm, a collection distance of 20 cm, a voltage of 23 kV, and a propulsion speed of 1.7 mL / h to obtain electrospun nanofibers.
[0081] (4) After the nanofibers in step (3) are carbonized and calcined, they are cooled and ground to obtain SiO 2 @C fiber.
[0082] The carbonization process is as follows: first, pre-oxidation at 200°C in air for 2 h, and then calcination at 900°C in a protective atmosphere for 2 h, with a heating rate of 3°C / min.
[0083] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain multi-pore carbon fiber materials.
[0084] Example 5
[0085] A method for preparing a multi-pore carbon fiber material comprises the following steps:
[0086] (1) NH3·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0087] Among them, NH 3 ·H 2 The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0088] (2) SiO 2 Nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0089] Among them, SiO 2 The mass ratio of nanospheres, polymethyl methacrylate (PMMA) and polyacrylonitrile was 3:3:5, the stirring temperature was 40°C, and the stirring time was 14 h.
[0090] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of the electrospinning needle of 0.4 mm, a collection distance of 12 cm, a voltage of 14 kV, and a propulsion speed of 0.9 mL / h to obtain electrospun nanofibers.
[0091] (4) After the nanofibers in step (3) are carbonized and calcined, they are cooled and ground to obtain SiO 2 @C fiber.
[0092] The carbonization process is as follows: first, pre-oxidation at 200°C in air for 2 h, and calcination at 750°C in a protective atmosphere for 3 h, with a heating rate of 3°C / min.
[0093] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain multi-pore carbon fiber materials.
[0094] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:
[0095] Comparative Example 1
[0096] A method for preparing a porous carbon fiber material comprises the following steps:
[0097] (1) Using polymethyl methacrylate (PMMA) as a template, polymethyl methacrylate (PMMA) and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0098] The mass ratio of polymethyl methacrylate (PMMA) to polyacrylonitrile is 1:1, the stirring temperature is 50°C, and the stirring time is 12 h.
[0099] (2) The spinning solution of step (1) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of an electrospinning needle of 0.6 mm, a collection distance of 15 cm, a voltage of 18 kV, and a propulsion speed of 1 mL / h to obtain electrospun nanofibers.
[0100] (3) After the nanofibers in step (2) are carbonized and calcined, they are cooled and ground to obtain porous carbon fibers.
[0101] The carbonization process is as follows: first pre-oxidation at 250°C in air for 2 h, calcination at 800°C in a protective atmosphere for 4 h, and a heating rate of 3°C / min.
[0102] Comparative Example 2
[0103] A method for preparing a porous carbon fiber material comprises the following steps:
[0104] (1) NH 3 ·H 2 O, ethanol and deionized water were mixed, and then tetrapropoxysilane was added into the mixed solution, stirred at 50 °C for 12 h, and centrifuged to obtain SiO 2 Nanospheres.
[0105] Among them, NH 3 ·H 2The volume ratio of O, ethanol and deionized water is 1:70:10, and the volume ratio of tetrapropoxysilane to the mixed solution is 7:80.
[0106] (2) SiO 2 As a template, SiO 2 The nanospheres and polyacrylonitrile are dissolved in N,N'-dimethylformamide and mixed to obtain a spinning solution.
[0107] Among them, SiO 2 The mass ratio of nanospheres to polyacrylonitrile was 1:1, the stirring temperature was 50°C, and the stirring time was 12 h.
[0108] (3) The spinning solution of step (2) was subjected to electrospinning at a temperature of 25° C., a humidity of 55%, an inner diameter of an electrospinning needle of 0.6 mm, a collection distance of 15 cm, a voltage of 18 kV, and a propulsion speed of 1 mL / h to obtain electrospun nanofibers.
[0109] (4) After the nanofibers in step (3) are carbonized and calcined, they are cooled and ground to obtain SiO 2 @C fiber.
[0110] The carbonization process is as follows: first pre-oxidation at 200°C in air for 2 h, calcination at 800°C in a protective atmosphere for 5 h, and a heating rate of 3°C / min.
[0111] (5) SiO 2 @C fibers were dispersed in a 1 mol / L NaOH aqueous solution and stirred for 12 h to etch the SiO 2 The nanospheres are centrifuged and dried to obtain porous carbon fiber materials.
[0112] The multi-porous carbon fibers prepared in Examples 1 to 5 are used to prepare negative electrode materials for sodium ion batteries. The morphology of the prepared multi-porous carbon fibers is characterized, and the results are as follows: Figure 1 , Figure 2 shown.
[0113] Depend on Figure 1 , Figure 2 It can be seen that the multi-aperture carbon fibers prepared in the present invention are interwoven into a three-dimensional network structure and have a uniform and dense pore structure.
[0114] Figure 3 This is a cross-sectional SEM image of a multi-aperture carbon fiber. It is observed that the internal pores of the carbon fiber are larger than 50 nm, which are SiO 2 Holes left after etching of nanospheres.
[0115] Figure 4This is a scanning electron microscope image of the longitudinal morphology of multi-pore carbon fibers, showing that there are obvious interconnected pore structures on the fiber surface and inside the fiber.
[0116] The porous carbon fiber materials prepared in Examples 1 to 4 and the porous carbon fiber material prepared using polymethyl methacrylate (PMMA) as a template in Comparative Example 1 were respectively made into working electrodes.
[0117] Specific method: Carbon fiber material, conductive carbon black, and binder polyvinylidene fluoride are mixed in a mass ratio of 8:1:1, N-methylpyrrolidone solvent is added to fully grind, and evenly coated on copper foil, and finally dried at 60°C and cut into electrode sheets with a diameter of 16 mm to obtain a working electrode.
[0118] Preparation of sodium ion battery: sodium sheet as positive electrode, glass fiber separator, 1 mol / L NaPF 6 The electrolyte and porous carbon fiber electrode sheet as the negative electrode are assembled into a button battery in a glove box.
[0119] Among them, the ratio of sodium hexafluorophosphate electrolyte: NaPF 6 Dissolved in an organic solvent with a volume ratio of EC:PC:FEC of 47.5:47.5:5 and a concentration of 1 mol / L.
[0120] The performance of the sodium ion battery obtained above was tested, and the results were as follows Figure 4 , Figure 5 shown.
[0121] Figure 5 The cycle comparison diagram of the sodium ion battery of the multi-porous carbon fiber material prepared in Examples 1 to 4 and the carbon fiber material with polymethyl methacrylate (PMMA) as a template prepared in Comparative Example 1; at a current density of 1 A / g, after 200 cycles, the specific capacity of Example 1 is 190 mAh g -1 The specific capacity of Example 2 is 169 mAh g -1 The specific capacity of Example 3 is 119 mAh g -1 The specific capacity of Example 4 is 129 mAh g -1 The specific capacity of comparative example 1 with PMMA as the single template is 79 mAh g -1 , proving the superiority of multi-porous carbon fibers in electrochemical performance over carbon fibers with a single template.
[0122] Figure 6 The figure is a comparison chart of the sodium ion battery rate performance of the multi-porous carbon fiber prepared in Examples 1 and 2 and that of Comparative Example 1. After 10 cycles at different current densities, when the current density returned to 100 mAh g -1 The specific capacity of Example 1 is 290 mAh g-1 The specific capacity of Example 2 is 259 mAh g -1 The specific capacity of comparative example 1 is 180 mAh g -1 , proving that multi-aperture carbon fibers have better rate performance.
[0123] Figure 7 The nitrogen adsorption-desorption curve of the multi-porous carbon fiber material prepared in Example 1 of the present invention shows that the adsorption amount is relatively high when the relative pressure is between 0.8 and 1.0, and a hysteresis loop appears, indicating that the multi-porous carbon fiber has more mesopores and macropores; Figure 8 The pore size distribution diagram of the multi-porous carbon fiber material of Example 1 of the present invention shows that the multi-porous carbon fiber also has mesopores or mesopores with an average pore diameter of 16 nm; the specific surface area of the multi-porous carbon fiber is 57.75 m 2 g -1 .
[0124] In summary, the multi-porous carbon fiber material of the present invention has a three-dimensional framework structure, which provides a transmission path for the transmission of electrons, enhances the conductivity of the material, and effectively reduces the local current density. The stable skeleton of the multi-porous carbon fiber material can buffer the volume changes produced during the charge and discharge process, further improving the electrochemical performance. When the multi-porous carbon fiber material is applied to the negative electrode material of the sodium ion battery, it exhibits good cycle stability.
[0125] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a multi-pore carbon fiber material, characterized in that: The following steps are involved: SiO2 nanospheres, polymethyl methacrylate and polyacrylonitrile were dissolved in N,N ’ - dimethylformamide, mixing at 30°C to 60°C to obtain a spinning solution, and electrospinning the spinning solution to obtain nanofibers; The nanofibers are pre-oxidized in air at 200°C to 250°C, and then heated to 500°C to 1000°C, and calcined in a protective atmosphere to decompose the polymethyl methacrylate in the nanofibers to obtain carbon fibers coated with SiO2; The SiO2 coated carbon fiber is stirred in an alkaline solution to etch the SiO2 to obtain a multi-pore carbon fiber material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the SiO2 nanospheres, polymethyl methacrylate and polyacrylonitrile is 1-5:1-5:
5.
3. The preparation method according to claim 1, characterized in that: The alkaline solution contains OH - The solution has a concentration of 0.5mol / L~2mol / L.
4. The preparation method according to claim 1, characterized in that: The stirring time is 6h to 24h.
5. The preparation method according to claim 1, characterized in that: The electrospinning conditions are as follows: temperature of 20°C to 40°C, humidity of 40% to 60%, inner diameter of the electrospinning needle of 0.21mm to 1.07mm, collection distance of 10cm to 25cm, voltage of 16kV to 25kV, and propulsion speed of 0.5mL / h to 1.5mL / h.
6. The preparation method according to claim 1, characterized in that: The pre-oxidation time is 2 hours, and the calcination time is 2 hours to 5 hours.
7. The preparation method according to claim 1, characterized in that: The heating rate is 1°C / min to 5°C / min.
8. A multi-pore carbon fiber material prepared by the preparation method according to any one of claims 1 to 7.
9. A sodium ion battery negative electrode material, characterized in that: It is prepared from active material, conductive carbon black and polyvinylidene fluoride, and the active material is the multi-porous carbon fiber material as claimed in claim 8.
10. A method for preparing the negative electrode material for a sodium ion battery according to claim 9, characterized in that: The following steps are involved: The porous carbon fiber material, conductive carbon black and polyvinylidene fluoride are mixed in a mass ratio of 7 to 8:1 to 2:1, N-methylpyrrolidone is added, the mixture is ground, the mixture is coated on a copper foil, dried and cut to obtain an electrode sheet.
Citation Information
Patent Citations
Silicon-carbon composite material with nano micropores and preparation method as well as application thereof
CN103311523A
Preparation method of carbon fiber material with adjustable pore diameter and porosity and carbon fiber material
CN105696114A
Hollow carbon sphere fiber and preparation method thereof
CN111962183A
MoS < 2 >-CoS < 2 >-porous carbon fiber composite material as well as preparation method and application thereof
CN117790706A
Low thermal conductivity carbon-containing materials and methods of producing the same
US20190257005A1